PENERAPAN PEMBELAJARAN KOOPERATIF DENGAN SIKLUS ACTIVITY, DISCUSSION, AND EXERCISE UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Novie Diana Putri; Martini Martini (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
This research aimed to describe the learning implementation, improvement of students’ learning outcomes, and students’ responses to the implementation of cooperative learning with the Activity, Discussion, and Exercise (ADE) cycle. This research used a pre-experimental with one group pretest and post-test design. The subject in this research were 30 students of VII-B SMPN 28 Surabaya. Data collection methods were by observations, tests, and questionnaires. The instruments used were observation sheets of learning implementation, tests, and students’ response questionnaires. The data analysis applied in this research were N-Gain and t-test to determine the improvement of students’ learning outcomes and Likert scale (percentage) on the implementation of learning and students’ response. The results indicated that the learning was carried out very well. The students’ learning outcome increased significantly with N-Gain score in moderate category. The students gave a positive response in learning implementation. The conclusion of this research was that the implementation of cooperative learning with the activity, discussion, and exercise cycle could improve the students’ learning outcome.